Pemberdayaan Perangkat Desa Jatimekar Jatiluhur Purwakarta melalui pelatihan Pembukuan Keuangan Sederhana - Oktapianti, Mila Sari (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
On October 16, 2021, Purwakarta held a simultaneous village head election party, many Village Heads nominate with various visions, missions and strategies to win the village head election. Furthermore, on October 18, 2021 as many as 170 elected Village Heads were officially inaugurated by the Regent of Purwakarta Hj. Anne Ratna Mustika, S.E, the elected Village Head must be able to adapt to the conditions and situations of the village apparatus, especially the elected Village Head is inexperienced or new. Not a few Jatiluhur Purwakarta Village apparatuses who still have limited knowledge of the bookkeeping system, including simple financial bookkeeping. The purpose of this PKM is to provide understanding and knowledge to the Jatimkar Village Apparatus on a simple financial bookkeeping system. The results of the PKM activity on Empowering Village Apparatus Jatiluhur Jatiluhur Purwakarta through the Simple Financial Bookkeeping training went well and smoothly, the participants were very enthusiastic, it could be seen from the village apparatus that they participated in all activities well and easily understood all the material provided by the PKM team. Starting from the stage of providing material, bookkeeping procedures, to the practice of making simple financial bookkeeping. After training in simple financial bookkeeping for village officials, Bumdes, Kadus, RT and RW, each party or village official in Jatimkar, Jatiluhur, Purwakarta Villages has been able to make simple financial reports that can be presented and easily understood by all, including the community.